2005
DOI: 10.1158/1541-7786.mcr-05-0082
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling Maps Loss of Heterozygosity and Defines the Timing and Stage Dependence of Epigenetic and Genetic Events in Wilms' Tumors

Abstract: To understand genetic and epigenetic pathways in Wilms' tumors, we carried out a genome scan for loss of heterozygosity (LOH) using Affymetrix 10K single nucleotide polymorphism (SNP) chips and supplemented the data with karyotype information. To score loss of imprinting (LOI) of the IGF2 gene, we assessed DNA methylation of the H19 5V differentially methylated region (DMR). Few chromosomal regions other than band 11p13 (WT1) were lost in Wilms' tumors from Denys-Drash and Wilms' tumor-aniridia syndromes, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 43 publications
(53 reference statements)
8
62
1
3
Order By: Relevance
“…Interestingly, most cases of 11p LOH in WT involve both the 11p13 and 11p15 regions (19), and although it was originally shown that the WT1 gene at 11p13 was not imprinted in kidney (20), we have subsequently shown that paternally expressed imprinted transcripts are transcribed from the WT1 locus. These imprinted transcripts are the noncoding antisense RNA WT1-AS (21) and the alternate coding transcript AWT1, which gives rise to NH 2 -terminally truncated WT1 proteins (22).…”
Section: Introductionmentioning
confidence: 75%
“…Interestingly, most cases of 11p LOH in WT involve both the 11p13 and 11p15 regions (19), and although it was originally shown that the WT1 gene at 11p13 was not imprinted in kidney (20), we have subsequently shown that paternally expressed imprinted transcripts are transcribed from the WT1 locus. These imprinted transcripts are the noncoding antisense RNA WT1-AS (21) and the alternate coding transcript AWT1, which gives rise to NH 2 -terminally truncated WT1 proteins (22).…”
Section: Introductionmentioning
confidence: 75%
“…Both methods detected similar incidence of IGF2 LOI. Yuan et al (28) used IGF2 LOI with methylation analysis of H19 DMR and SNP arrays. In contrast, Fukuzawa et al used a methylation analysis of two imprinted regions of 11p15.5, H19 DMR and KvDMR1, to detect it.…”
Section: Discussionmentioning
confidence: 99%
“…The ranges of each abnormality in Caucasians indicate the lowest and highest values reported in the previous studies. (5,7,8,18,28) …”
Section: Discussionmentioning
confidence: 99%
“…Several additional studies of RCC have also indicated that the loss of 4q is associated with sarcomatoid transformation and high-grade tumors (Jiang et al, 1998;Yoshimoto et al, 2007). In Wilms' tumors, a 2.4-Mb minimal region of loss of heterozygosity has been detected at 4q24-q25 by 10K SNP array, which is a CXXC4 and progression of RCC T Kojima et al region that includes the CXXC4 gene (Yuan et al, 2005). Interestingly, loss of 4q has been detected in 46-77% of colon, cervix and hepatocellular carcinomas (Mitra et al, 1994;Ried et al, 1996;Yeh et al, 1996) suggesting that aberrant Wnt signaling may be implicated in the formation of several cancer types.…”
Section: Discussionmentioning
confidence: 99%